2002
DOI: 10.1016/s0034-4257(01)00289-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel algorithms for remote estimation of vegetation fraction

Abstract: Spectral properties of a wheat canopy with vegetation fraction (VF) from 0% to 100% in visible and near-infrared (NIR) ranges of the spectrum were studied in order to devise a technique for remote estimation of VF. When VF was < 60%, from emergence till middle of the elongation stage, four distinct, and quite independent, spectral bands of reflectance existed in the visible range of the spectrum: 400 to 500 nm, 530 to 600 nm, near 670 nm, and around 700 nm. When VF was between 60% and 100%, reflectance in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
662
3
35

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,611 publications
(712 citation statements)
references
References 40 publications
12
662
3
35
Order By: Relevance
“…Moreover, FVC is extensively applied in fields such as agriculture, forestry, resource and environmental management, disaster risk monitoring, and drought monitoring (Gitelson et al, 2002;Purevdorj et al, 1998) Accurate estimation of the FVC is required for research on land-surface processes, climate change, and numerical weather prediction (Zeng et al, 2000). Representatively, the FVC was applied in soil erosion models (RUSLE (Revised Universal Soil Loss Equation), SEMMA (Soil Erosion Model for Mountain Areas), and GeoWEPP (Geospatial interface for WEPP)) and atmospheric models (NOAH Land-Surface Model and NAM (North American Mesoscale) Eta model) (Choi et al, 2014;Gutman and Ignatov, 1998).…”
Section: Fvc (Fractional Vegetationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, FVC is extensively applied in fields such as agriculture, forestry, resource and environmental management, disaster risk monitoring, and drought monitoring (Gitelson et al, 2002;Purevdorj et al, 1998) Accurate estimation of the FVC is required for research on land-surface processes, climate change, and numerical weather prediction (Zeng et al, 2000). Representatively, the FVC was applied in soil erosion models (RUSLE (Revised Universal Soil Loss Equation), SEMMA (Soil Erosion Model for Mountain Areas), and GeoWEPP (Geospatial interface for WEPP)) and atmospheric models (NOAH Land-Surface Model and NAM (North American Mesoscale) Eta model) (Choi et al, 2014;Gutman and Ignatov, 1998).…”
Section: Fvc (Fractional Vegetationmentioning
confidence: 99%
“…Information derived from VIs is usually less sensitive to illumination and other factors affecting reflectance (Gitelson et al, 2002). The underlying mechanisms of VIs are well understood, and they emphasize some features of vegetation cover and facilitate obtaining relevant information from digital imagery (Delegido et al, 2013).…”
Section: Fvc (Fractional Vegetationmentioning
confidence: 99%
“…During crop development there is usually a gradual increase in crown cover and remote sensing can detect these changes. Gitelson et al (2002) used spectral VIs to estimate cover fraction for wheat and corn.…”
Section: Phenologymentioning
confidence: 99%
“…Domestic digital cameras measure the intensity of reflectance in the red (R), green (G) and blue (B) bands, and thus provide an inexpensive alternative method for measuring a crop's N status. Gitelson et al [7] suggested that the intensity of green and red reflectance could be used to as an alternative to red and infrared reflectance to measure canopy properties. When the digital images were captured in controllable and constant light environment, there could precisely predict SPAD readings [8].…”
Section: Introductionmentioning
confidence: 99%